2005
DOI: 10.3171/jns.2005.102.2.0202
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical workforce trends in the United States

Abstract: The number of recruitment advertisements for neurosurgeons during the last 5 years has increased significantly, concomitant with a severe decline in the number of active neurosurgeons and a static supply of residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The availability of neurosurgeons across the United States has dwindled as the rates of graduating neurosurgical residents has failed to catch up with the growth of the US population, with demand currently skyrocketing (55). For example, Bryne et al reports that with fewer trauma neurosurgeons available in Cook County, time to treatment for patients with emergent neurosurgical issues has increased (56).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of neurosurgeons across the United States has dwindled as the rates of graduating neurosurgical residents has failed to catch up with the growth of the US population, with demand currently skyrocketing (55). For example, Bryne et al reports that with fewer trauma neurosurgeons available in Cook County, time to treatment for patients with emergent neurosurgical issues has increased (56).…”
Section: Discussionmentioning
confidence: 99%
“…A decade ago, Seifer et al 19 also analyzed demand for physicians using advertisements, and recommended repeat studies as a timely and accurate way to determine marketplace trends. Since then, others have examined trends in neurosurgery 21,22 and diagnostic radiology. 30,31 A recent study suggested that the ratio of specialists to generalists was stable between 1993 and 1999, but did not report advertisements for hospitalists or trends within specialties.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies, some of which also examined trends in surgical and pediatric advertisements, [19][20][21][22][23] we focused our abstraction process on advertisements for internal medicine and internal medicine subspecialties.…”
Section: Advertisement Selectionmentioning
confidence: 99%
“…Neurosurgical data suggest that approximately 130 residents complete their training each year. 7 All are trained in basic spine surgery and many in more complex spinal reconstruction. One might reasonably ask: are we turning out the best possible product and fulfilling a society need?…”
Section: General Issues Facing Spine Surgery and Spine Surgeonsmentioning
confidence: 99%